2019
DOI: 10.1186/s12961-019-0463-9
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Theoretical Domains Framework to understand knowledge broker decisions in selecting evidence for knowledge translation in low- and middle-income countries

Abstract: Background Health-related organisations disseminate an abundance of clinical and implementation evidence that has potential to improve health outcomes in low- and middle-income countries (LMICs), but little is known about what influences a user decision to select particular evidence for action. Knowledge brokers (KBs) play a part as intermediaries supporting evidence-informed health policy and practice by selecting and synthesising evidence for research users, and therefore understanding the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 40 publications
(61 reference statements)
0
31
0
Order By: Relevance
“…As the results of this study demonstrated, managers' lack of access to knowledge resources and workload are among the barriers that prevent knowledge implementation. The results of other studies confirm these findings and emphasize barriers such as lack of time (having multiple responsibilities and attending meetings) to apply knowledge [49], insufficient skills and newness to work processes [50,51], and the language of the journal that is mainly English [52]. To eliminate these barriers, it is necessary to provide managers with a summary of knowledge resources.…”
Section: Discussionmentioning
confidence: 64%
“…As the results of this study demonstrated, managers' lack of access to knowledge resources and workload are among the barriers that prevent knowledge implementation. The results of other studies confirm these findings and emphasize barriers such as lack of time (having multiple responsibilities and attending meetings) to apply knowledge [49], insufficient skills and newness to work processes [50,51], and the language of the journal that is mainly English [52]. To eliminate these barriers, it is necessary to provide managers with a summary of knowledge resources.…”
Section: Discussionmentioning
confidence: 64%
“…[ 26 ] According to one pilot study, 75% of lifetime cases of diagnosable mental disorders began by the age of 24. [ 27 ] This research survey on MHC is not a substitute for treatment but will create awareness. Hopefully, it will help to motivate some resources that could lead students to happier and healthier university lives.…”
Section: Discussionmentioning
confidence: 99%
“…The TDF identifies key factors supporting behaviour change in clinicians to inform strategies to enhance the uptake of evidence-based practice [ 21 , 22 , 25 ]. Once factors associated with the utilisation of evidence-based pathways are identified, interventions can be designed to increase KT [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about KT and sepsis pathways [ 28 ] and no known KT studies exist focusing on paediatric sepsis and nurses. Nurses’ perceptions and engagement are key to successful KT [ 26 ] of clinical pathways. To advance knowledge and application of evidence-based practice, we introduced a Paediatric Sepsis Pathway (PSP), including targeted education for nurses on paediatric sepsis recognition, escalation and management, and on how to translate the PSP into practice.…”
Section: Introductionmentioning
confidence: 99%